Differences in the Incidence of Anemia in Acceptors of 1-Month Injection and 3-Month Injection Contraceptives - Arlya Balqis Rachman; Sulistiawati; Ratna Dwi Jayanti (PROFESSIONAL HEALTH JOURNAL, 2025)
Background : Anemia is a condition in which there is a reduced number of red blood cells or a lower concentration of hemoglobin within them. Injectable contraception is the most widely utilized hormonal option. Research clearly indicates that heavy or prolonged menstruation serves as a major trigger for iron deficiency anemia in women of childbearing age. The 1-month and 3-month injectable contraceptives contain hormones that notably affect menstrual patterns. This study aims to analyze the differences in the incidence of anemia between users of the 1-month and 3-month injectable contraceptives. Method : This research method is observational analytic design with a comparative approach. The number of sample is 62 injectable contraceptive users, selected through consecutive sampling techniques. Hemoglobin levels were carefully examined as the measurement instrument. Data analysis was conducted using the Independent sample t-test and Chi-Square. Results : The results clearly demonstrate that among users of the 1-month injectable contraceptive, the majority exhibited regular menstrual patterns (40.3%). In contrast, most users of the 3-month injectable method experienced secondary amenorrhea (43.5%). Additionally, a significant proportion of respondents were found to be non-anemic (64.5%). The Independent sample t-test revealed a p-value of 0.025 (p < 0.05). The chi-square test presented a p-value of 0.598 (>0.05). Conclusion : There is a difference in hemoglobin levels in acceptors of 1-month and 3-month injectable contraceptives. There is no difference in the incidence of anemia in acceptors of 1-month and 3-month injectable contraceptives.